Blackbox Testing terhadap Prototipe Sistem Monitoring Kualitas Air Berbasis IoT - Anggita Nur Fathoni; Unan Yusmaniar Oktiawati (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2021)
Internet of Things is a combination of hardware and software which can carry out a communication between the two. The application of this system can be utilized to monitor water quality with temperature and pH parameters online through Blynk application. Blynk application shows data from the reading results of two sensors, namely the DS18B20 temperature sensor and the DFRobot pH sensors in the form of number and graphs. Prior to further use, the accuracy of both of sensors was examined in order to gain more accurate sensor readings. The accuracy testing resulted in an average relative error value of 0,98% for the DS18B20 temperature sensor and 0,95% for DFRobot pH sensor. In the testing, blackbox testing was used to make more use of functional things in the system designed for the user convenience in monitoring water quality based on the the application’s display. Furthermore, the system shows that the function of the hardware or Blynk application to monitor temperature and pH conditions has been running well and can be utilized by the users easily and beneficially.